Evaluation of the impact of patient input in health technology assessments at NICE. (29th January 2021) - Livingstone, Heidi; Verdiel, Vassilia; Crosbie, Helen; Upadhyaya, Sheela; Harris, Kevin; Thomas, Lizzie
Abstract: Objective: Accounts of patient experiences are increasingly used in health technology assessment (HTA) processes. However, we know little about their impact on the decision-making process. This study aims to assess the level and the type of impact of patient input to highly specialised technologies (HSTs) and interventional procedures (IPs) guidance at the National Institute for Health and Care Excellence (NICE). Methods: A questionnaire was developed to capture quantitative and qualitative data on the amount and type of impact of patient input into NICE HTAs. It was completed by committee members of the guidance-producing programs after a discussion of the considered topics. The data were analyzed by topic and overall, for each program, and compared across programs. Results: Patient input was assessed on ten pieces of HST guidance published between January 2015 and November 2019, and on twenty-six pieces of IP guidance scoped between February 2016 and October 2018. A total of 96 responses were collected for HST and 440 for IP. The level of impact of patient input was higher for HST than for IP. For HST, no respondents stated that it had no impact, whereas in IP, 35 percent of respondents did. The most common types of impact found for HST and IP were that it helped interpret the other evidence and that it provided new evidence. Conclusions: The impact of patient input is not necessarily explicit in changing recommendations, but it provides context, reassurance, and new information to the committee for the decision-making process in HTAs.